Vitamin D status and chronic obstructive pulmonary disease: a prospective general population study. - Tea Skaaby (Public Library of Science (PLoS), 2014)
Objectives Vitamin D deficiency is common among persons with chronic obstructive pulmonary disease (COPD). Whether vitamin D affects the development and deterioration of COPD or is a consequence of the disease lacks clarity. We investigated the association between vitamin D status and prevalent and incident COPD in the general population. Methods We included a total of 12,041 individuals from three general population studies conducted in 1993-94, 1999-2001, and 2006-2008, respectively, with vitamin D measurements. Information on COPD was obtained from the Danish National Patient Register and The Danish Registry of Causes of Death. Results There were 85 prevalent and 463 incident cases of COPD (median follow-up 9.7 years). We found a statistically significant inverse association between vitamin D status and prevalent COPD with odds ratio = 0.89 (95% confidence interval, CI: 0.79, 1.0), but no statistically significant association with incident COPD with a hazard ratio = 0.98 (95% CI: 0.94, 1.0), respectively, per 10 nmol/l higher vitamin D status, when adjusted for possible confounders. Conclusions We found a statistically significant inverse cross-sectional association between vitamin D status and COPD, but no association between vitamin D status and incident COPD.